Penerapan Range of Motion (ROM) Pasif terhadap Peningkatan Kekuatan Otot Pada Pasien Stroke Non Hemoragik di RSI PKU Muhammadiyah Pekajangan Pekalongan - Kartikasari, Dian; Fidiastuti, Fidiastuti (MAHESA : Malahayati Health Student Journal, 2024)
ABSTRACT Stroke is a cerebrovascular disease (brain blood vessels) due to the death of brain tissue (cerebral infarction). The cause of stroke is reduced blood and oxygen flow to the brain due to blockage, constriction or rupture of brain blood vessels which causes symptoms of hemiparase’s weakness of the limbs. Implementation of Range of Motion (ROM) exercise can be carried out in non-hemorrhagic stroke patients with physical mobility problems. ROM exercises can cause stimulation so that increasing chemical and neuromuscular activity which has an effect on increasing muscle strength, and is useful for improving muscle tone, preventing joint stiffness, improving blood circulation and increasing joint mobilization. Implementation of ROM exercises in stroke patients is very important at promoting patient independence. Gradual recovery of the extremities through ROM exercises can help achieve a level of independence and reduce the impact of weakening strength on daily activities.This study aims to determine implementation of Range of Motion (ROM) exercise is useful for increasing muscle strength in non-hemorrhagic stroke patients at RSI PKU Muhammadiyah Pekajangan Pekalongan. Descriptive research design in the form of a case study with a nursing process approach by implementing nursing on physical mobility disorders in non-hemorrhagic stroke patients by doing ROM exercises. The case subject is one subject with a medical diagnosis of non-hemorrhagic stroke at RSI PKU Muhammadiyah Pekajangan. The results of this study showed that the patient's muscle strength increased from 3 to 4 and from 2 to 3 after being given ROM exercise for 3 x 24 hours. There is an effect of impelementation Range of Motion (ROM) on increasing muscle strength in non-hemorrhagic stroke patients, because patients ha increased in muscle strength scale after being given ROM exercises. Keywords: Range of Motion, Muscle Strength, Stroke  ABSTRAK Akibat dari stroke dapat menimbulkan hemiparise dan kelemahan anggota gerak yang menimbulkan masalah gangguan mobilita fisik. Guna memelihara dan meningkatkan kekuatan otot, mobilitas sendi, mencegah kekakuan sendi, memperbaiki tonus otot, dan memperlancar sirkulasi darah maka diperlukan latihan Range of Motion (ROM). Pemulihan  ekstremitas secara bertahap melalui latihan ROM bisa membantu mencapai tingkat kemandirian dan mengurangi dampak melemahnya kekuatan pada aktivitas sehari-hari. Penelitian ini bertujuan untuk mengetahui sejauh mana penerapan Range of Motion (ROM) bermanfaat untuk meningkatkan kekuatan otot pada pasien stroke non hemoragik di RSI PKU Muhammadiyah Pekajangan Pekalongan. Desain penelitian deskriptif dalam bentuk studi kasus dengan pendekatan proses keperawatan dengan mengimplementasikan keperawatan pada gangguan mobilitas fisik pada pasien stroke non dengan melakukan latihan ROM. Adapun subyek kasus adalah satu kasus dengan diagnosa medis stroke non hemoragik di RSI PKU Muhammadiyah Pekajangan. Hasil penelitian menunjukkan bahwa kekuatan otot pasien setelah diberikan latihan ROM selama 3x 24 jam mengalami peningkatan dari 3 ke 4 dan dari 2 ke 3. Terdapat pengaruh penerapan Range of Motion (ROM) terhadap peningkatan kekuatan otot pada pasien stroke non hemoragik, karena pasien mengalami peningkatan skala kekuatan otot setelah diberikan latihan ROM. Kata Kunci: Range Of Motion, Kekuatan Otot, Stroke